Sosialisasi dan Pemberdayaan Remaja sebagai Upaya Pencegahan HIV/AIDS - Indra Rahmad; julhana julhana; Aniharyati; Fadlurahmi (CV. CENDIKIA JENIUS INDONESIA, 2026)
HIV/AIDS remains a significant public health threat among adolescents due to limited knowledge and risky behaviors; this community service activity aims to improve the knowledge of adolescents and health workers about HIV/AIDS prevention. This activity used a quasi-experimental one-group pretest-posttest design involving 30 adolescents and 10 health workers in Jatibaru Village, Bima City. Education was delivered through interactive lectures, educational videos, and booklets. Knowledge was measured using a validated questionnaire administered before and after the intervention. Data were analyzed descriptively and using a paired sample t-test with a significance level of p<0.05. The results showed a significant increase in the average knowledge score of adolescents from 58.7±12.4 to 84.5±8.7 (mean difference of 25.8 points, p=0.000). The proportion of adolescents with good knowledge increased from 26.7% to 83.3%, while those with poor knowledge decreased from 33.3% to 0%. Health cadres' knowledge also increased by 23.0 points. Community-based HIV/AIDS education using a multimedia approach effectively increased the knowledge of adolescents and cadres and supported sustainable HIV/AIDS prevention at the community level.